Police and Crime Commissioners : The Transformation of Police Accountability - Caless, Jane; Owens, Jane (Book collections on Project MUSE., 2016)
Police and Crime Commissioners (PCCs) are elected representatives whose role is to ensure that police forces in England and Wales are running effectively. Intended to bring a public voice to policing and hold the police to account, the holders of this controversial role also control budgets and strategic planning. Bryn Caless and Jane Owens obtained unprecedented access to the PCCs and their chief police officer teams and undertook confidential interviews with both sides. The results reveal the innermost workings of the PCCs' relationships with the police, media, partners and public. The authors analyse the election process (in which PCCs polled the lowest local mandate ever) and consider the future of this politically-contested role. Examining the PCCs' impact on policing, this fascinating book makes essential reading for Police Crime Commissioners, chief officers, police officers, police trainers and academics, students and researchers in criminology and policing.